PEMANFAATAN GENERATIVE AI DALAM PEMBUATAN PERANGKAT PEMBELAJARAN: WORKSHOP UNTUK GURU SMK NEGERI 10 SURABAYA - Nurcahyawati, Vivine; Rahmawati, Endra (Universitas Mataram, 2024)
One of the fast-growing technologies that has great potential in the world of education is artificial intelligence. (Artificial Intelligence). The workshop aims to enhance teachers' understanding and skills in using Artificial Intelligence, the ChatGPT and Tome.App applications, to develop more interesting and effective learning plans and create more innovative material presentations. The method of this activity begins with conducting surveys to understand the needs and challenges faced by teachers in using Artificial Intelligence technology. Next, a workshop module is set up to guide the workshop participants. Evaluation instruments are also prepared to measure participants' understanding before and after the workshop, as well as to assess participants' satisfaction with the overall performance of the workshop. The evaluation results showed a significant improvement in participants' understanding of the material after attending the workshop. Based on pre-test and post-test data, the average answer accuracy increased from 55% to 86%. Besides, the participants' response to the workshop was also very positive, with the majority of participants giving a